2010
DOI: 10.1111/j.1365-2958.2010.07292.x
|View full text |Cite
|
Sign up to set email alerts
|

Dimerization and DNA-dependent aggregation of the Escherichia coli nucleoid protein and chaperone CbpA

Abstract: The Escherichia coli curved DNA-binding protein A (CbpA) is a nucleoid-associated DNA-binding factor and chaperone that is expressed at high levels as cells enter stationary phase. Using a combination of genetics, biochemistry, structural modelling and single-molecule atomic force microscopy we have examined dimerization of, and DNA binding by, CbpA. Our data show that CbpA dimerization is driven by a hydrophobic surface comprising amino acid side chains W287 and L290 located on the same side of an α helix clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 28 publications
(52 reference statements)
0
48
0
Order By: Relevance
“…The DnaJ domain protein pTAC5 (protein GRMZM2G031721_ P0) was abundant in nucleoids, but it did not pass our criteria to be a candidate nucleoid protein. Escherichia coli nucleoids contain a DnaJ-related protein, CbpA, with DNA-binding activity involved in DNA aggregation that protects DNA from degradation by nucleases (Cosgriff et al, 2010). Therefore, it seems possible that some of the nucleoid-localized DnaJ domain proteins interact directly with DNA.…”
Section: Proteins Involved In Transcription and Rna Metabolismmentioning
confidence: 99%
“…The DnaJ domain protein pTAC5 (protein GRMZM2G031721_ P0) was abundant in nucleoids, but it did not pass our criteria to be a candidate nucleoid protein. Escherichia coli nucleoids contain a DnaJ-related protein, CbpA, with DNA-binding activity involved in DNA aggregation that protects DNA from degradation by nucleases (Cosgriff et al, 2010). Therefore, it seems possible that some of the nucleoid-localized DnaJ domain proteins interact directly with DNA.…”
Section: Proteins Involved In Transcription and Rna Metabolismmentioning
confidence: 99%
“…With circular plasmid DNA FIS binds at crossovers [36] stabilising a negatively supercoiled plectoneme with right-handed DNA coils (Figure 2). However at the tyrT UAS regulatory region three FIS dimers constrain a left-handed toroidal loop [31].…”
Section: Fismentioning
confidence: 99%
“…9 This work revealed that the CbpA-CbpM system was amenable to analysis using the bacterial twohybrid (BACTH) assay system that detects proteinprotein interactions in vivo. 15 Note that this system relies on the fact that the E. coli cyaA− strain BTH101 is unable to produce cAMP and thus has a Lac− phenotype.…”
Section: In Vivo and In Vitro Assays To Detect Cbpa-cbpm Interactionsmentioning
confidence: 99%
“…Our previous work also demonstrated that CbpA forms aggregates when bound to DNA that can be detected in vitro using gel shift assays. 9 Figure 1b-ii shows the outcome of such an experiment. Addition of CbpA to plasmid DNA results in the formation of aggregates that are trapped in the wells of the gel (compare lanes 1 and 2).…”
Section: In Vivo and In Vitro Assays To Detect Cbpa-cbpm Interactionsmentioning
confidence: 99%
See 1 more Smart Citation